PENGARUH SUHU DAN WAKTU EKSTRAKSI DAUN BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP AKTIVITAS ANTIOKSIDAN DENGAN METODE ULTRASONIC ASSISTED EXTRACTION (UAE) - Andriani, Meysi; Permana, I Dewa Gde Mayun; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 3 (2019): Jurnal ITEPA, 2019)
This research was conducted to determine the effect of temperature and time of extraction wuluh starfruit leaves on antioxidant activity using the ultrasonic assisted extraction method and to get the right temperature and time to produce extracts of wuluh starfruit leaf extract had highest antioxidant activity. Experiment used in this study is a Completely Randomized Design of factorial pattern with two factors, namely temperature and time. The first factor is the extraction temperature consisting of 3 levels, namely 30°C, 40°C, and 50°C. The second factor is the extraction time consisting of 3 levels, namely 10 minutes, 20 minutes, and 30 minutes. The research was repeated twice for obtaining 18 experimental units. The parameters observed in this study included yield, total phenol, total flavonoids, total tannin and antioxidant activity. The data obtained were analyzed by variance and if the treatment had significant effect followed by Duncan test. The results showed that the treatment of temperature and extraction time had a significant effect (P<0.05) on total phenol, total flavonoids, total tannin and antioxidant activity, but  no significant effect (P>0.05) on yield. The best results showed a temperature of 40°C with a time of 20 minutes having the highest antioxidant activity based on the percentage of free radical inhibition of 89.66% with an IC50 value of 25.74 mg/L, a yield of 15.49%, a total phenol of 437.79 mgGAE/g extract, total flavonoids was 393.00 mgQE/g extract, and total tannins was 402.27 mgTAE/g. Keywords : wuluh starfruit leaves,   temperature, time, ultrasonics, antioxidant